Consequências emocionais de um episódio de estupro na vida de mulheres adultas - Souza, Flávia Bello Costa de (2013)
Violence against women affects thousands of victims, regardless of age, culture and socioeconomic status. It is a public health problem with far-reaching consequences, both physical and psychological, which may be long-lasting. One type of sexual violence is rape. This qualiquantitative research aims at understanding the emotional consequences of a rape episode in a woman s life, as well as investigating the occurrence of post-traumatic stress disorder (PTSD), depression and self-esteem levels, and their correlation with sociodemographic data, specific characteristics of a rape and feelings of shame and guilt. Interviews were conducted with 37 women victims of rape under medical treatment at the Public Health Service in Perola Byington Hospital, São Paulo, Brazil. The instruments used were a semi-structured interview script, the Post-Traumatic Stress Disorder Checklist Civilian Version PCL-C (BERGER et al., 2004), the Beck Depression Inventory BDI (CUNHA, 2011) and the Rosenberg Self-Esteem Scale (DINI et al., 2004). Based on the compiled data, among other factors the study detected a significant statistical correlation between levels of depression and the presence of PTSD. Results indicated that the rape episode had effects such as sleep quality alterations, increased sense of fear of having contracted some disease, concern on being judged by others, difficulties in interpersonal relationships and negative impact on sexual life quality, apart from shame, guilt and negative self-perception of themselves and their bodies. In contrast, familiar, social and religious support and acceptance as well as individual behaviors of resilience proved to be positive and protective factors as regards to the victims